Respon Petani Terhadap Fluktuasi Harga Lada di Kecamatan Air Gegas Kabupaten Bangka Selatan: Farmers’ Response to Pepper Price Fluctuations in Air Gegas Subdistrict, South Bangka Regency - Adezia, Ferna; Setiawan, Iwan; Atmaja, Eddy Jajang Jaya (Journal of Integrated Agribusiness, 2025)
Fluctuating pepper prices tend to affect farmers' response to pepper, resulting in the amount of pepper production and post-harvest handling of pepper going down. In addition, fluctuations in pepper prices are also very influential for farmers on their daily needs. The objectives of this research are 1) Describe the response of farmers to pepper price fluctuations in production and post-harvest aspects in Air Gegas District, South Bangka Regency, and 2) Determine the impact of pepper price fluctuations for farmers in Air Gegas District, South Bangka Regency. This research was conducted using the survey method. Sampling used purposive sampling with a total sample of 68 respondents. Both data were analyzed by descriptive statistics. The results showed that the cognitive response of farmers to pepper price fluctuations in Air Gegas Subdistrict was categorized as high with a percentage of 69.63%. cognitive response is seen the level of understanding and knowledge about pepper price fluctuations. Affective response is the attitude, assessment and feelings of respondent farmers towards fluctuations in pepper prices is categorized as high with a percentage of 67.02%. Conative response is the action, desire, and tendency to behave farmers categorized as high with a percentage of 65.07%. The impact of pepper price fluctuations on pepper farmers in Air Gegas Subdistrict is classified as agreeing with a percentage of 70.17%.